Effect of thiacloprid on early life stages of common carp (Cyprinus carpio) - Velisek, Josef; Stara, Alzbeta (Chemosphere, 2018)
Toxicity of the neonicotinoid pesticide thiacloprid to embryos and larvae of common carp Cyprinus carpio was assessed under laboratory conditions. Carp embryos and larvae were exposed to thiacloprid at four concentrations: 4.5 (environmental concentration), 45, 225, and 450 μg/L for 35 days and compared to a non-treated control group. The effects on lipid peroxidation, antioxidant enzyme levels (superoxide dismutase, glutathione reductase, catalase, glutathione S-transferase, and reduced glutathione), mortality, growth, development, and histopathogenesis were assessed. Thiacloprid at tested concentrations were not associated with negative effects on hatching, behaviour, embryo viability, or Fulton's condition factor. Carp exposed to 45 μg/L thiacloprid showed lower weight and length compared to controls. Thiacloprid at 225 and 450 μg/L delayed development and led to lower weight and length of carp. Significantly lower superoxide dismutase and glutathione reductase activity was observed at all tested concentrations of thiacloprid compared with the control group. Chronic thiacloprid exposure of early-life stages of carp affected ontogeny and growth rate, and inhibited antioxidant capacity.
Keywords: chemické látky znečišťující vodu; Embryo, Nonmammalian; Pesticides; antioxidancia; Neonicotinoid; pesticidy; Embryo; Larvae; Thiazines; vztah mezi dávkou a účinkem léčiva; Water Pollutants, Chemical; thiaziny; kapři; Neonicotinoids; larva; Animals; Antioxidants; zvířata; Carps; Histopathology; peroxidace lipidů; Early development; Lipid Peroxidation; Larva; Dose-Response Relationship, Drug; Antioxidant biomarkers; neonikotinoidy; embryo nesavčí